PEMANFAATAN KULIT MANGGIS DAN RUMPUT LAUT DALAM PEMBUATAN PERMEN JELLY - Alamin Hidayat; Vonny Setiaries Johan; Raswen Efendi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The aims of this study to get the best ratio of mangosteen peel and seaweed to produce jelly candies with good quality. This study was held experimentally using CRD (Complete Randomized Design) of five treatments and three replications. The treatment were JKR1 (ratio mangosteen peel and seaweed 2 : 1), JKR2 (ratio mangosteen peel and seaweed 3 : 2), JKR3 (ratio mangosteen peel and seaweed 1 : 1), JKR4 (ratio mangosteen peel and seaweed 2 : 3) and JKR5 (ratio mangosteen peel and seaweed 1 : 2). Data were analized by ANOVA and DNMRT at the level of 5%. The result showed that there was significant influence (P<0,05) of ratio mangosteen peel and seaweed in ash content, crude fiber content, reducing sugar content and organoleptic test, but no significant influence (P>0,05) in moisture content. The ratio of mangosteen peel and seaweed in the treatment JKR3 (mangosteen peel and seaweed ratio 1:1) was best treated with a moisture content 26.51%, ash content 0.75%, crude fiber content 2.22%, reducing sugar content 9.45%, antioxidant content 21.06 µg/ml. The result of sensory analysis of JKR3 were a little bit reddish purple colour, very sweetness taste, the texture was springy and overall assesment of jelly candy was preferred by the panelists. Keywords: Mangosteen peel, seaweed, jelly candy